Measuring the effectiveness of advertising and R&D on firm performance using the Generalized Least Squares (SLS) model in the Philippine setting - Bunagan, Kathryn Anne P.; Eliot, Bianca Marie R.
Empirical literature on the relationship between marketing variables and intangible investments and indicators of firm performance mostly come from foreign sources. Local literature that studies how advertising expenditures (a marketing variable) and research and development (an intangible investment) are linked to the performance of a firm is limited. This paper contributes to local literature by testing for the significant relationship between 1) advertising expenditures and sales revenue, and advertising expenditures and a firm’s financial performance 2) R&D expenditures and sales revenue, and R&D expenditures and a firm’s financial performance. The paper uses data from 2012 - 2021 on 67 firms listed in the Philippine Stock Exchange (PSE), and employs random effects (RE) estimation given the nature of the data obtained from Reuters Eikon and PSE Edge. The estimation model is also structured based on the assumption that the individual-specific intercepts in the regression equation are dispersed at random and that the effects of the independent variables are constant for all subjects over all periods of time. The results provide strong evidence that changes in advertising spending and R&D expenditure have a significant positive effect on the Return on Assets of a firm, the indicator used in this paper as a measure of firm performance. The study, however, obtains insufficient evidence that support the hypothesis that changes in advertising spending and R&D expenditure exhibit a significant positive effect on the sales revenue of a firm.